Pengembangan Media Flashcard Berbasis Augmented reality untuk Meningkatkan Kemampuan Pemecahan Masalah Pecahan Kelas IV - Putra, Susetya Dwi; Andrijati, Noening; Nurharini, Atip (Jurnal Gentala Pendidikan Dasar, 2025)
This research aims to develop and evaluate the feasibility, practicality, and effectiveness of augmented reality-based flashcard media in enhancing students' problem-solving skills in fractions. Utilizing the Plomp development model, the study was conducted during the second semester of the 2024/2025 academic year in four public elementary schools in the Wijayakusuma cluster, Semarang City. A pretest-posttest control group design with simple random sampling was employed. The problem-solving ability test was aligned with Polya's indicators. The findings indicate that the augmented reality-based flashcard media is highly feasible, achieving an average feasibility score of 92.98%. Assessments based on media validation, material validation, and practicality all fell into the very feasible category. The practicality test yielded a score of 91.52% from both teachers' and students' responses, indicating high practicality. Effectiveness testing through pretests and posttests showed significant improvement in problem-solving abilities, with a significance value of 0.000 in the t-Test. N-Gain analysis revealed that the flashcard media was more effective than conventional learning, with a control class N-Gain of 0.5796 and an experimental class N-Gain of 0.7090. In conclusion, augmented reality-based flashcard media effectively enhances students' mathematical problem-solving skills in fractions and serves as an alternative solution to improve the quality of fourth-grade learning.